Transplant International Official Journal of the European Society for Organ Transplantation 1992
DOI: 10.1007/978-3-642-77423-2_30
|View full text |Cite
|
Sign up to set email alerts
|

FK506 mechanism of nephrotoxicity: stimulatory effect on endothelin secretion by cultured kidney cells

Abstract: The administration of FK506 or cyclosporin A (CyA) to animals and humans induces a decrease in glomerular filtration rate and renal plasma flow and an increase in renal vascular resistance. Endothelins (ET-1), very powerful renal vasoconstrictors, are involved in CyA-related alteration in renal haemodynamics. In this study we sought to determine whether FK506 and CyA had a stimulatory effect on endothelin secretion by cultured kidney cells (tubular and mesangial cells) and whether this stimulatory effect coinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…We have reported that FK 506 increased the production of ET-1 and the levels of ET-1 mRNA in human vascular endothelial cells. 10 Moutabarrik et al 34 also reported that FK 506 increased the secretion of ET-1 from cultured kidney cells and that oral administration of FK 506 elevated plasma ET-1 concentrations. The synthesis of bioactive ET-1 requires a recently cloned phosphoramidon-sensitive ECE.…”
Section: Discussionmentioning
confidence: 97%
“…We have reported that FK 506 increased the production of ET-1 and the levels of ET-1 mRNA in human vascular endothelial cells. 10 Moutabarrik et al 34 also reported that FK 506 increased the secretion of ET-1 from cultured kidney cells and that oral administration of FK 506 elevated plasma ET-1 concentrations. The synthesis of bioactive ET-1 requires a recently cloned phosphoramidon-sensitive ECE.…”
Section: Discussionmentioning
confidence: 97%
“…CsA also stimulates the release of endothelin-1 (ET-1) from endothelial, tubular, and mesangial cells (4,5) in rats and has been associated with increased expression of angiotensin II (ANG II) type I receptors in the kidney. Activation of each of these pathways could promote an increase in renal vascular tone.…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of pregnancy complications is not surprising given that cyclosporine and FK506 cause hypertension and renal insufficiency. [8][9][10][11][19][20][21][22][23][24][25][26][27][28][29][30][31][32] These agents cause systemic and afferent arteriolar vasoconstriction by increasing the production of endothelin and thromboxane A 2 and interfering with nitric oxide-mediated vasodilation. [19][20][21][22][23] The afferent arteriolar vasoconstriction results in significant reductions in glomerular filtration rate and renal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Chronic nephropathy also contributes to the renal insufficiency and is characterized by arteriolar hyalinosis, global glomerulosclerosis, proximal tubule damage, and tubulointerstitial fibrosis. [25][26][27][28][29][30] This report describes the hemodynamics and pregnancy outcomes after orthotopic liver transplantation at our institution. Subjects 2 (during her second pregnancy), 3, 4, and 5 all had abnormally elevated CO during the first or early second trimesters.…”
Section: Discussionmentioning
confidence: 99%